Women and politics - Caudhurī, Nājamā, 1942-; Begum, Hamida A.; Islam, Mahmuda; Mahtab, Nazmunnessa; Women for Women (Organization : Bangladesh) (Dhaka : Women for Women, 1994)
Collection of papers presented at convention on Women and Politics.
Cover title: Women & politics.
Includes bibliographical references.
Keywords: Feminism -- India; Women -- Political activity -- India; Women -- India -- Social conditions